НОРАВШАН МОДЕЛЛАР АСОСИДА ЎЗАРО БОҒЛАНГАН ЧОРРАҲАЛАРДА ТРАНСПОРТ ОҚИМЛАРИНИ БОШҚАРИШ - Жалелов, Р.М. (SCIENCE and SOCIETY, 2021)
City intersection traffic signal control is an important method to improve the efficiency of road network and alleviate traffic congestion. This paper addresses the design and implementation of an intelligent traffic lights controller based on fuzzy logic technology.